Intense and localized export of selected marine snow types at eddy edges in the South Atlantic Ocean - A. Accardo; R. Laxenaire; R. Laxenaire; A. Baudena; S. Speich; S. Speich; R. Kiko; L. Stemmann; L. Stemmann (Biogeosciences, 2025)
The biological carbon pump (BCP) comprises a wide variety of processes involved in transferring organic carbon from the surface to the deep ocean. This results in long-term carbon sequestration. Without the BCP, atmospheric CO2 concentrations would be around 200 ppm higher. This study reveals that ocean dynamics at the mesoscale and submesoscale could have a major impact on particulate organic matter (POM) vertical distribution. Our results indicate that intense submesoscale frontal regions, such as those between mesoscale eddies, could lead to an important accumulation and transport of POM from the mixed-layer depth (MLD) down to the mesopelagic zone. To reach these conclusions, a multifaceted approach was applied. It included in situ measurements and marine snow images from a BGC-Argo float equipped with an Underwater Vision Profiler (UVP6), satellite altimetry data, and Lagrangian diagnostics. We focused our study on three intense features in marine snow distribution, observed during the 17-month-long float mission in the Cape Basin in the southwest of Africa. These features were located in the frontal region between mesoscale eddies. Our study suggests that a particle injection pump induced by a frontogenesis-driven mechanism has the potential to enhance the effectiveness of the biological pump by increasing the depth at which carbon is injected into the water column. This work also emphasizes the importance of establishing repeated sampling campaigns targeting the interface zones between eddies. This could improve our understanding of the mechanisms involved in the deep accumulation of marine snow observed at eddy interfaces.